Роль чорноморських козаків у формуванні козацьких військ в Південній Бессарабії в першій половині ХІХ ст. - Бачинська, О. (Чорноморська минувшина, 2007)
У статті на основі архівних документів розглянуто питання про перебування чорноморських козаків на території межиріччя Дністра та Дунаю, з’ясовано їх роль у формуванні козацьких військ, показано постаті чорноморців за їх біографічними описами. On the basis of the archive documents the problems concerning the presence of the Black Sea Cossacks on the territory between the Dnister and the Danube have been considered in the article, as well as their role in forming of the Cossack troops in South Bessarabia has been cleared up, the personal descriptions of the Black Sea Cossacks according to their biographies have been presented.